2006
DOI: 10.1055/s-2006-926606
|View full text |Cite
|
Sign up to set email alerts
|

Ist die Entfernung der Membrana limitans interna (ILM) immer erforderlich bei Patienten mit dem therapierefraktären diffusen diabetischen Makulaödem ohne Nachweis von epimakulären Proliferationen?

Abstract: Vitrectomy with or without ILM peeling may improve BCVA and decrease foveal thickness. ILM peeling was not found to enhance the improvement of VA postoperatively. A larger study is required to determine whether ILM peeling is essential in surgery for DME without epimacular proliferation or cellophane maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…ILM peeling has been used in some cases of refractory diabetic macular edema (DME) after failed intravitreal injections of anti-VEGF, steroids, and/or laser photocoagulation, with decrease in foveal thickness but with no improvement of visual acuity postoperatively [ 160 – 163 ]. In branch and central retinal vein occlusion-associated macular edema, there are few series of selected cases that show improvement in visual acuity after PPV with the removal of preretinal hyaloid and peeling of the ILM [ 164 166 ].…”
Section: Indications For Macular Peelingmentioning
confidence: 99%
“…ILM peeling has been used in some cases of refractory diabetic macular edema (DME) after failed intravitreal injections of anti-VEGF, steroids, and/or laser photocoagulation, with decrease in foveal thickness but with no improvement of visual acuity postoperatively [ 160 – 163 ]. In branch and central retinal vein occlusion-associated macular edema, there are few series of selected cases that show improvement in visual acuity after PPV with the removal of preretinal hyaloid and peeling of the ILM [ 164 166 ].…”
Section: Indications For Macular Peelingmentioning
confidence: 99%
“…In Academy, the bene t of ILM peeling for the patients undergoing PPV for DME is still a dilemma (26, 27 difference between the groups in the rst 6 months, they reported that the decrease in foveal thickness and macular volume was statistically signi cantly higher in the group with ILM peeling in the following period (15). Aboutable reported in a study on patients with diffuse DME without epimacular membranes, ILM peeling reduced foveal thickness and did not improve visual acuity improvement compared to nonpeeling (11). Bahadir et al reported in their randomized controlled study that ILM peeling did not cause a signi cant improvement in visual acuity compared to non-peeling in patients who underwent PPV for DME treatment (16).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are many studies in the literature claiming that ILM peeling is bene cial in the presence of vitreomacular traction (VMT) in patients with diabetic retinopathy, the bene t of performing this procedure in the absence of VMT is controversial (9)(10)(11)(12)(13)(14)(15)(16). There are some randomized studies demostrated that ILM peeling had unfavourable outcomes, such as statistically signi cant absolute microscotomas within the central retinal area (17).…”
Section: Introductionmentioning
confidence: 99%